3D particle size distribution of inter-ground Portland limestone/slag cement from 2D observations: Characterization and distribution evaluation. (30th August 2017) - Sun, Hongfang; Fan, Bing; Memon, Shazim Ali; Cen, Zhuo; Gao, Xiaobin; Lin, Bin; Liu, Bing; Li, Dawang; Xing, Feng; Zhang, Xiaogang
Highlights: 2D PSD of limestone, slag, and OPC in PLC (-S) binders was determined by BSE. Using 2D data and a discrete stereology, the 3D PSD was reconstructed. Inter-grinding makes the binder particles coarser and distribution broader. Inter-grinding of PLC (-S) binders benefits the particle packing. Abstract: In this research, the particle size distribution (PSD) of different components in inter-ground Portland limestone cement (PLC) and limestone-slag cement (PLC-S) was characterization by using an electron microscopy approach. Firstly, the 2D PSD of limestone, slag, and Portland cement (OPC) was determined by means of image analysis. Based on the 2D data and using a discrete stereology, the 3D size distribution was reconstructed. Finally, the PSD of inter-ground mixtures was assessed by using a compressible packing model. The results showed that the addition of limestone in cement makes the OPC component coarser and distribution broader; meanwhile, the limestone particles were found to be finer than the OPC particles. The addition of both limestone and slag (PLC-S) were found to further broaden the PSD of OPC component and limestone component with the mean size of particles increased in the following order (limestone < slag < OPC). Among the tested samples, the packing density of OPC was the lowest while the packing density of PLC-S was found to be the highest. Based on test results, it can be concluded that the addition of more components during inter-grinding makes the particle size of binder coarser and distribution broader, which in turn, benefits the particle packing and possibly improves the mechanical and durability performance of the cement based composites.